МАКЕДОНСКОТО ЈАЗИЧНО ПРАШАЊЕ ВО ЛИТЕРАТУРНИОТ 19 ВЕК (Filološke pripombe, 2019)
In the beginning of the 19-in century the question of abolition of the Archbishopric of Ohrid was popularized, and at the same time the fight against the terror of the Ottoman Empire began and for freedom of our own state, for standardization of literary language and affirmation of Macedonian identity. In order to decide about the Macedonian language issue, in 19-th century there were operations towards few activities: the first group of Macedonian intellectuals began to write and publish their own personal works in Macedonian folk language versus old Slavonic language. The second group started with oral and written polemics about resolving the Macedonian language issue. The third group began to open a printing house and started printing books, textbooks, dictionaries, almanacs and newspapers in Macedonian folk language. The fourth group encompassed those who directly started the codification of Macedonian literary language over their textbook, dictionaries and Grammar book. The fifth group started to take interest in translation activity. The sixth group turned toward exercising Macedonian language on the theater stage, but for realization of these activities funds were necessary, and as a result the seventh group was engaged in strengthening the role of church-school community, which was essential instigator of education and revolution in Macedonia in 19-th century. To that end, the eight group including intellectualsrevolutionaries, started to form associations, always attributing the label literature to the name of the association so that revolutionary ideology can be covered with the veil of literature. Discord among Macedonian intellectuals resulted from that: some of them were for evolution and the others for revolution. However, the aim was the same: freedom for Macedonia. Therefore, whenever we speak about Macedonian language, Macedonian literature, church songs, revolution or history of Macedonia in the 19-th century, we actually speak about the same: Macedonian identity, Macedonian name, Macedonian literature, culture and historic plenitudes.